Reformasi Sistem Rekrutmen dan Pemberhentian Hakim Konstitusi dalam Perspektif Bangalore Principles of Judicial Conduct - Muhammad Zelvan Farend; Agus Riwanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2026)
The non-procedural dismissal of Constitutional Court Justice (CCJ) Aswanto by the House of Representatives demonstrates a serious threat to judicial independence and reveals fundamental problems in the system of judicial recruitment. This study employs normative legal research. The issues examined concern how a CCJ can be dismissed non-procedurally during an active term and replaced through an equally flawed mechanism, as well as how weaknesses in the recruitment system and ethical oversight contribute to such practices. This research applies a normative, case-based, and conseptual approach. The Constitutional Court Law, and the cases surrounding the dismissal of Aswanto and the appointment of Guntur Hamzah, including the decision of the Honorary Council of the Constitutional Court (MKMK) which confirmed a violation of integrity values. The findings indicate that Aswanto dismissal lacked a solid legal basis, weakened judicial independence, and potentially violated the principle of legal certainty. The appointment of the replacement justice was also procedurally defective and adversely affected the legitimacy and independence of the Constitutional Court (MK). Accordingly, the root problem lies in the misinterpretation of the Constitutional Court Law, necessitating a reconstruction of the judicial selection mechanism and the strengthening of ethical oversight of CCJ.